2023
DOI: 10.3390/ijms24021783
|View full text |Cite
|
Sign up to set email alerts
|

Alarmins and MicroRNAs, a New Axis in the Genesis of Respiratory Diseases: Possible Therapeutic Implications

Abstract: It is well ascertained that airway inflammation has a key role in the genesis of numerous respiratory pathologies, including asthma, chronic obstructive pulmonary disease, and acute respiratory distress syndrome. Pulmonary tissue inflammation and anti-inflammatory responses implicate an intricate relationship between local and infiltrating immune cells and structural pulmonary cells. Alarmins are endogenic proteins discharged after cell injury in the extracellular microenvironment. The purpose of our review is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 180 publications
0
4
0
Order By: Relevance
“…MicroRNAs are small, noncoding molecules of about twenty-two nucleotides and have crucial roles in both healthy and pathological cells; in fact, they are involved in various intra-and intercellular mechanisms like proliferation and apoptosis, so their incorrect function is involved in the onset of different diseases, such as cancer [1,2]. In detail, a miRNA could have a lot of genes as targets and, at the same time, a gene could be regulated by different miRNAs [3]; according to the scientific literature, they control about 60% of human genes [4].…”
Section: Introduction 1general Considerations On Mirnasmentioning
confidence: 99%
“…MicroRNAs are small, noncoding molecules of about twenty-two nucleotides and have crucial roles in both healthy and pathological cells; in fact, they are involved in various intra-and intercellular mechanisms like proliferation and apoptosis, so their incorrect function is involved in the onset of different diseases, such as cancer [1,2]. In detail, a miRNA could have a lot of genes as targets and, at the same time, a gene could be regulated by different miRNAs [3]; according to the scientific literature, they control about 60% of human genes [4].…”
Section: Introduction 1general Considerations On Mirnasmentioning
confidence: 99%
“…IL-33 drives Th2-associated cytokine production in children [ 40 ] and adults [ 41 ] with allergic asthma. In addition, some authors have demonstrated its role in food allergy.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on humans confirmed the importance of alarmins in IgE-mediated allergies: serum concentrations of TSLP and IL-25 are found to be increased in patients with food allergy [ 40 ], and IL-25 levels appear to correlate positively with atopic severe phenotypes [ 43 ]. TSLP and IL-33 could also play a role in the development of tolerance in humans [ 41 ], and their expression in the oral mucosa would be influenced by the microbiome [ 42 ]. Fecal calprotectin levels appear to be significantly elevated in patients with food allergies, which decrease after an exclusion diet [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…[79][80][81] HMGB1 levels were negatively correlated with lung function in asthmatic patients. [82][83][84] This means that HMGB1 may be a potential biomarker of asthma severity. 85 In addition, inhibition of HMGB1 protects human bronchial epithelial cells (HBE) by alleviating TDI-induced asthma via ROS/AMPK/autophagy pathway.…”
Section: The Role and Related Pathways Of Hmgb1 In Asthmamentioning
confidence: 99%
“…It is reported that HMGB1 levels in sputum of asthmatic patients are significantly increased and positively correlated with asthma severity, obesity, and neutrophil percentage and significantly increased in lung tissue and bronchoalveolar lavage fluid (BALF) of asthmatic rats induced by ovalbumin (OVA) and positively correlated with obesity 79–81 . HMGB1 levels were negatively correlated with lung function in asthmatic patients 82–84 . This means that HMGB1 may be a potential biomarker of asthma severity 85 .…”
Section: The Role and Related Pathways Of Hmgb1 In Asthmamentioning
confidence: 99%